Effect of a home- made milk replacer on pre-weaning performance of Nubian male kids - .Elkhair, Anfal; Abdalla, I.A; El Obied, G.H (Gezira Journal of Agricultural Science; Vol 15 No 2 (2017), 2017)
The use of milk replacers to substitute valuable whole milk for suckler goat kids is not widely practiced in the Sudan. The aim of this study was to investigate the effect of two levels of a home-made milk replacer on pre-weaning kid performance, milk consumption, live weight gain, mortality rate and weaning age. Twenty four Nubian male kids of 3 days average age and 3 kg mean live weight were randomly allocated to three treatments each containing 8 kids. Two treatments were offered home- made milk replacer prepared from tallow, egg, groundnut cakes, glucose, minerals and vitamins. Treatment (A) reared on 50% milk replacer and 50% goat milk, while Treatment (B ) on 75% milk replacer and 25% goat milk.  Treatment(C) was offered whole goat milk and used as a control. All kids were offered goat milk for 3 days as adaptation period. Then, each treatment was offered the allocated experimental milk twice daily through plastic bottle feeders of 500 ml capacity at 8 am and 4 pm. The consumption of milk was measured daily for seven weeks. Body weight and mortality rate were recorded weekly. Samples of milk replacer and goat milk were analyzed for total solid, protein, fat, sugar, ash and acidity. The results revealed that, total solids, protein, fat and acidity were significantly (P<0.05) higher in treatment (C) than (A) and (B), however, ash was significantly (P<0.05) higher in treatments (A) and (B) than (C).In addition sugar was not significantly different among treatments. Mortality rate was highest in treatment (B) with 100% increase when compared to (A) and (C) 37.5%.  Milk consumption, feed conversion efficiency, weight gain, and weaning age were not significantly different among  treatments (A) and (C).The study concluded that goat milk could be replaced by50% home-made milk replacer without any deleterious effects on performance of Nubian kids.         استخدام بدائل اللبن كبديل اللبن الطبيعي في تغذية جديان الماعز لا يمارس على نطاق واسع في السودان. الهدف من هذه الدراسة معرفة أثر بديل اللبن المصنع منزلياً على أداء جديان  الماعز قبل الفطام و المتناول من اللبن و زيادة الوزن الحي و معدل النقوق وعمر الفطام . استخدمت 24 من جديان الماعز النوبي (ذكور) في أعمار ثلاثة أيام كمتوسط  ومتوسط وزن 3كجم، وتم توزيعها عشوائياً إلى ثلاث معاملات  كل معامله تحتوي على ثمانية من  جديان الماعز .  تمت تغذية مجموعتين  أ و ب على البديل المصنع منزلياً الذي تم تجهيزه من الدهن الحيواني و بيض دجاج و أمياز الفول السوداني و جلكوز و أملاح معدنية وفيتامينات. المعاملة  الاولى (أ) غذيت على 50% من بديل اللبني  و 50% من لبن الماعز و المعاملة  الثانية (ب) غذيت على 75% من بديل اللبني و 25% من لبن الماعز أما المعاملة  الثالثة (ج) غذيت على لبن الماعز والتي  تمثل الشاهد. كل الجديان أعطيت لبن الماعز لمده ثلاثة أيام كفترة أقلمه. غذيت   كل المعاملات التجريبية، مرتين يومياً صباحاً ومساءً  بواسطه رضاعة بلاستكية  سعه 500 مل عند الساعة الثامنة صباحاً والرابعة عصراً.  قيس استهلاك اللبن  يومياً لمدة سبعة أسابيع و الوزن الحي ومعدل النقوق أسبوعياً. كل عينات اللبن خضعت لتحليل  كل من المواد الصلبة و البروتين و الدهن و السكر و الرماد  والحموضة. أوضحت النتائج ان هنالك فروقات معنويه على مستوى ((P≤0.05 في كل من الجوامد الكلية والبروتين والدهون والحموضة بين  المعاملة ج والمعاملة  ب حيث انها كانت أعلى في المعاملة ج. بينما كان الرماد أعلى معنوياً  ( p≤ 0.05)  في المعاملة أ وب  بالنسبة لمستوى السكر في المعاملات لا توجد فروقات معنوية بين المعاملات .اما نسبه النقوق كانت اعلى في المعاملة ب  حيث بلغت 100% مقارنه مع كل من المعاملتين ) أ(و)ج(والتي تمتل.37.5% . قبل الفطام اظهرت النتائج عدم وجود فروقات معنويه بين المعاملات في كلا من المستهلك من اللبن و معدل الكفاءة التحويلية و الزيادة  في الوزن وعمر الفطام . خلصت  الدراسة الي انه  يمكن  استخدام 50% بديل اللبن  من غير اي تأثير ضار على أداء جديان الماعز النوبي .